Cr3+ and Nd3+ co-activated garnet phosphor for NIR super broadband pc-LED application. (July 2022) - He, Shuai; Zhang, Liangliang; Zhang, Jingnan; Hao, Zhendong; Wu, Hao; Wu, Huajun; Luo, Yongshi; Pan, Guohui; Liu, Feng; Zhang, Jiahua
Highlights: An efficient super broadband NIR phosphor is achieved by doping Nd 3+ in Ca2 LuZr2 Al3 O12 : Cr 3+ . The spectral range is extended and the IQE is improved due to efficient energy transfer from Cr 3+ to the highly efficient Nd 3+, in CLZA: Cr 3+, Nd 3+ phosphors. Strong emission bands of Nd 3+ with quantum efficiency close to 100% are observed, at around 900 nm and 1060 nm, which are complementary to Yb 3+ emission, at 1030 nm. An efficient super broadband NIR pc-LED with 350 nm bandwidth is achieved, in which the blend of CLZA: Cr 3+, Nd 3+ and CLZA: Cr 3+, Yb 3+ phosphors are fluorescence converter. Abstract: Near-infrared phosphor converted light emitting diodes (NIR pc-LEDs), as a compact light source, play a constructive role in wearable optical biosensing devices. In order to detect the properties of different substances, the NIR emission should be as wide as possible. The typical strategy for broadening the band is the superposition emission of Cr 3+ and Yb 3+, the bandwidth of which is 300–320 nm, and it needs to be further broadened. In this paper, NIR Ca2 LuZr2 Al3 O12 garnet phosphor, co-activated by Cr 3+ and Nd 3+, is prepared. The emission quantum efficiencies of Nd 3+ at 900 nm and 1060 nm are close to 100%, and the emission band is complementary to that of Yb 3+ at 1030 nm. An efficient super broadband NIR pc-LEDs (47.6 mW@100 mA), with the bandwidth of 350 nm, are achieved. The bandwidth and the efficiency of the pc-LEDs are improved greatly, compared with other reported ones. Graphical abstract: Image, graphical abstract